Inter-individual differences in repair of DNA base oxidation, measured in vitro with the comet assay - Andrew Collins (2001)
There is a need for a reliable, robust and sensitive assay for DNA repair, suitable for use with human lymphocyte samples in molecular epidemiological investigations. The comet assay (single cell alkaline gel electrophoresis) has been modified to measure the ability of a simple subcellular extract of lymphocytes to carry out the initial step of repair, i.e. incision, on a DNA substrate carrying specific lesions—namely, oxidized bases introduced by visible light in the presence of photosensitizer. The cell extract is free of non-specific nuclease activity, incising DNA only if the DNA has been treated with photosensitizer and light. The activity varies between individuals, but consistency is seen between samples from each individual taken on occasions several months apart. The lack of activity of extract from Ogg1– mouse cells (deficient in the glycosylase that excises 8-oxoguanine) in this assay confirms that the activity measured is predominantly excision repair of oxidized bases. This new DNA repair assay is simple, rapid and requires only small quantities of lymphocyte extract (obtainable from 10 ml blood).